PENINGKATAN LITERASI DAN PENGELOLAAN KEUANGAN MELALUI SOSIALISASI INTERAKTIF BAGI PEMUDA PEMUDI DI DESA PUSPANEGARA - Mugi Rahayuningsih; Naena Devi Zulkarnaen; Siti Nur Septi; Lely Fahzia Hidayati; Intan Rahma Sari (Publika Citra Media, 2026)
Financial literacy and financial management are essential skills that young generations need to face future economic challenges. However, in many areas, including Kampung Kebon Kopi Mandiri, the level of financial literacy among youths remains relatively low. This condition is reflected in the limited understanding of budget planning, basic transaction recording, and transparent organizational fund management. Such limitations have an impact on the suboptimal administration of youth activities, particularly in terms of accountability and financial planning. The Community Service Program (PMKM) was implemented as an effort to enhance financial literacy and financial management skills among the youths of Kampung Kebon Kopi Mandiri. Through an interactive socialization approach, participants were introduced to fundamental financial concepts, the importance of transaction recording, and effective budgeting methods. The activities were delivered through material presentations, group discussions, and financial recording simulations relevant to the operations of the local youth organization (Karang Taruna).The results of the program indicate an improvement in participants' understanding of orderly and accountable financial management. This program is expected to serve as an initial step for the youths of Kampung Kebon Kopi Mandiri in developing a culture of better and more sustainable financial management.